Analysis of Sanitation Technology for Waste Management and Drainage Using the Analytical Hierarchy Process (AHP) Method in Bangko City - Astri Yulia; Denny Helard; Vera Surtia Bachtiar (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
Sanitation in Indonesia is defined as efforts to dispose of liquid waste and domestic waste to create a clean and healthy living environment both at the household and settlement levels Domestic waste management needs to be considered in managing a settlement Domestic waste products, especially those containing human feces, contain dangerous pathogens. If it is released directly into water bodies without processing it will result in environmental pollution Technology and knowledge are needed to accelerate the implementation of development states that technology options are highly dependent on technical and non-technical aspects; environmental factors, cultural and behavioral factors, as well as capital and recurring cost factors To analyze the choice of technology, determined based on perception using the Process Hierarchy Analysis (AHP) method. the AHP method can be used in determining sanitation technology in specific areas in order to obtain the most suitable sanitation technology for use in specific areas. The selected sanitation technology is a recommendation that is acceptable to the local population. Based on this, in order to accelerate the implementation of development, it is necessary to determine the right choice of sanitation technology for slum settlements in Bangko City, Merangin Regency. The selection of sanitation technology in the most effective waste treatment technology in Bangko uses the AHP method, namely conducting sewage treatment by suctioning feces with 31% and good drainage by making grase traps as much as 28%.